Epidemiology of injuries in racket sports: a cross-sectional study of specific injuries within one olympic cycle - Lambert, C.; Banerjee, M.; Ritzmann, R.; Lachmann, D.; Wolfarth, B.; Grim, C.; Shafizadeh, S.; Geßlein, M.; Peters, N.; Reinert, N. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Objective Despite the growing interest in racket sports, injury prevalence, circumstances and severity as a function of gender, performance level and return to play have not been investigated to date. The aim was therefore to evaluate the occurrence of sport-specific injuries from a quantitative and qualitative perspective in the Olympic disciplines Tennis, Badminton and Table Tennis.